Getting in a Bind - Comparing Executive Compensation Regulations in the US and the UK - Reddy, Bobby V (Apollo - University of Cambridge Repository, 2024)
Executive compensation is a topical issue on both sides of the Atlantic, with concerns that the pay of managers of US and UK publicly traded companies has spiralled out of control. However, a minority narrative has emerged that a discrepancy in pay levels favoring executives of US over UK companies is leading to corporations shunning the London Stock Exchange and an exodus of talent from the UK to the US. When determining the reasons for cross-border pay variations, regulation is an obvious candidate for blame, but is it the only piece of the puzzle? In this article, US and UK executive compensation regulations are compared, finding that the UK does indeed have a stricter regulatory environment, with, in particular, shareholders being given a binding “say-on-pay” in contrast to a simple advisory vote in the US. The divergence in pay levels between the US and the UK cannot, though, solely be attributed to differences in regulations, and cultural attitudes toward high pay also play a role, together with the general outperformance of the US exchanges in recent years. It is easy to get in a bind over regulations, but with executive compensation, other factors are also at play.